Lean Manufacturing and Six Sigma Critical Success Factors -A Case Study of the Moroccan Aeronautic Industry - Raja Elboq; Mustapha Hlyal; Jamila El Alami (International Journal of Supply Chain Management, 2020)
Companies are constantly striving to achieve a highest rate of competitiveness. Thus, they implement either Lean manufacturing or Six sigma approach or both. However, their successful implementation is a real challenge. Hence, one of the proven tools to take up this challenge is a set of critical success factors (CSFs). This study provides a comparative statement of the recommendations suggested by every CSF from the perspective of each approach and examines how far the CSFs determine the successful implementation of Lean manufacturing and Six sigma in the Moroccan aeronautics industry. Also, based on a qualitative research methodology it assesses the importance assigned to each CSFs for each approach. The results would provide aeronautics managers with indicators and guidelines for a successful simultaneous implementation of Lean principles and Six Sigma techniques.